2017
DOI: 10.1177/0194599816688647
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose‐Derived Mesenchymal Stem Cells for Osseous Rehabilitation of Induced Osteoradionecrosis: A Rodent Model

Abstract: Objective Human adipose-derived mesenchymal stem cells (ADSCs) were used to rehabilitate bone damaged by osteoradionecrosis (ORN) in an established animal model. Study Design Prospective animal study. Setting Academic department laboratory. Subjects and Methods After institutional review board and Institutional Animal Care and Use Committee approval, 24 athymic nude rats were divided into 5 groups: 4 groups irradiated (20 Gy) by brachytherapy catheter placed at the left hemimandible and 1 mock irradiation cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
0
19
0
3
Order By: Relevance
“…ORN can be treated conservatively, using antibiotic and hyperbaric oxygen therapies, but aggressive cases are a clinical challenge that may include substantial surgical resection . Mesenchymal stem cells (MSCs) have been the subject of extensive investigation in the past few decades, including in association with bone regeneration after traumas and neoplasia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORN can be treated conservatively, using antibiotic and hyperbaric oxygen therapies, but aggressive cases are a clinical challenge that may include substantial surgical resection . Mesenchymal stem cells (MSCs) have been the subject of extensive investigation in the past few decades, including in association with bone regeneration after traumas and neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al observed in an animal model of ORN that a combined application of rat (r)MSCs and bone morphogenetic protein (BMP)‐2 led to improved bone healing after post‐irradiation dentoalveolar trauma in rats compared to BMP‐2 applied alone. Other positive results showing increased bone deposition or preservation after the application of human adipose tissue‐derived stem cells (ADSCs) to an induced mandibular osteoradionecrosis model in rats have been demonstrated using histological and radiological evaluations . However, there are few reports of investigations demonstrating the effects of cell therapy after irradiation in bones other than femur and mandible.…”
Section: Introductionmentioning
confidence: 99%
“…Specific interventions vary widely and depend on the location and degree of fibrosis; these include physiotherapy, massage, progressive occupational therapy, botulinum toxin A injection, microcurrent therapy, mesenchymal stem cell therapy, and surgical treatment. At this time, no existing method of treatment offers complete remission …”
Section: Introductionmentioning
confidence: 99%
“…At this time, no existing method of treatment offers complete remission. 1,7,8 There has been success in treatment of postradiation fibrosis of patients with breast cancer with topical superoxide dismutase (SOD), indicated by a decrease in pain scores and in the area of fibrosis. 9 SOD is an enzyme found in various tissues throughout the body and has a fundamental role in the elimination of reactive oxidative species and free radicals that cause tissue damage and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In case surgery is required during drug intake, specific rules are to be followed. A possible complication is bisphosphonate-related osteonecrosis of the jaw (BRONJ) manifesting as exposed, nonvital bone that does not recover over 8 weeks after current or past bisphosphonate therapy (6,7,8,9,10,11,12) The mains steps included in the Germany clinical protocol for dental sanitation and care in patients receiving or planned to receive bisphosphonate therapy are as follows: (13,14,15)…”
Section: Introductionmentioning
confidence: 99%